Relevansi Mukjizat Al-Qur’an sebagai Solusi Tantangan Zaman: Dari Masa Kenabian hingga Era Digital - Irsyadillah, Muhammad; Renaldy, Ahmad; Putri Amalia, Citra; Nurpanada; Prasetya Jayadi, Awal Prasetya Jayadi; Hastuti (Al-Mau’izhoh: Jurnal Pendidikan Agama Islam, 2025)
The Qur'an, as the holy book of Islam, is believed to contain eternal miracles that remain relevant across all eras. This study aims to explore the continuity of the Qur'an's miraculous nature in addressing modern challenges, from the prophetic era to the digital age. Using a qualitative-descriptive method with a literature review and content analysis approach, this research examines various dimensions of the Qur'anic miracle, including linguistic, scientific, ethical, and technological aspects. The findings reveal that the Qur'an not only offers rhetorical beauty and unique linguistic structure but also contains scientific signs and moral values capable of responding to developments in knowledge, digital technology, and shifting cultural paradigms in modern society. The digitalization of the Qur'an through online applications, interactive platforms, and artificial intelligence has expanded public access to divine revelation, yet it also presents new challenges regarding depth of understanding, accuracy of interpretation, and ethical engagement with the sacred text. This study concludes that understanding the Qur'an's miracle requires an integrative and contextual approach to ensure it remains a relevant and practical solution for Muslims facing the spiritual, intellectual, social, and technological disruptions of contemporary times.